Capital flows and financial crises - Kahler, Miles, 1949- (Cornell University Press, 1998)
Capital flows to the developing economies have long displayed a boom-and-bust pattern. Rarely has the cycle turned as abruptly as it did in the 1990s, however: surges in lending were followed by the Mexican peso crisis of 1994-95 and the sudden collapse of currencies in Asia in 1997. This volume maps a new and uncertain financial landscape, one in which volatile private capital flows and fragile banking systems produce sudden reversals of fortune for governments and economies. This environment creates dilemmas for both national policymakers who confront the "mixed blessing" of capital inflows and the international institutions that manage the recurrent crises. The authors-leading economists and political scientists-examine private capital flows and their consequences in Latin America, Pacific Asia, and East Europe, placing current cycles of lending in historical perspective. National governments have used a variety of strategies to deal with capital-account instability. The authors evaluate those responses, prescribe new alternatives, and consider whether the new circumstances require novel international policies